The Use of Paravertebral Analgesia in the Management of Pain in the Elderly Patient With Rib Fractures. Issue 12 (December 2020) - Wasfie, Tarik; Howell, Adam; Cwalina, N; Yapchai, Raquel; Hille, Jennifer; Hella, Jennifer; Shapiro, Brian; Barber, Kimberly R.
Background: Elderly patients with rib fractures carry a high morbidity rate, particularly due to pulmonary complications as decreased respiratory efforts ensue secondary to pain. Risk of bleeds in the elderly on anticoagulant therapy is high. The effort to reduce narcotic use in patients is now a health care priority. We propose that the use of paravertebral analgesia (PVA) pumps is an alternative pain control method with less risk and easy placement. Methods: Two hundred and seventy-nine patients were admitted with multiple fractured ribs to the Trauma Center of Community Hospital and treated with the application of continuous PVA via a pump (72 patients). Pain scores were recorded before and after the initiation of the pump. These patients were compared with a group of the remaining 207 patients who received intravenous narcotics only. Results: The mean change from baseline in pain scores for all patients was 1.43 (SD = 2.75). The mean change in pain for the treatment group was 1.93 (SD = 2.60), and the change in pain for the control group was 1.24 (SD = 2.79). Change in pain differed between groups (1.3 vs 1.8; P = .01) although it was a small difference. After adjusting for age, gender, Injury Severity Score, Glasgow Coma Scale, number of fractures, and comorbid conditions, there was no significant difference in pain post-procedure (odds ratio = 0.75; P = 0.39) with an effect size of 30% and total sample size of 279. Conclusion: The PVA pump using bupivacaine is an effective safe and alternative method for managing elderly patients with rib fractures eliminating the serious side effects associated with narcotics.